La actividad física programada y la salud en los adultos mayores del club abuelitos en movimiento del barrio Obrapía, Loja 2016-2017 - Quezada Iñahuazo, Wellington Hipolito (2018)
The present investigation titled THE PHYSICAL ACTIVITY PROGRAM AND THE HEALTH IN THE ELDERLY ADULTS OF THE THE CLUB "GRANDPARENTS IN MOVEMENT" OF THE OBRAPIA DISTRICT, LOJA 2016-2017. Whose problem is, how does the scheduled physical activity affect the health and quality of life of the senior citizens of the club "grandparents in movement"club in the Obrapia neighborhood? To comply with the aforementioned problem, set a general objective, diagnose the incidence of physical activity programmed in health and quality of life in the elderly of the club "grandparents in movement". Which led us to seek and apply the best methodologies such as the scientific method, the inductive method, the fragmentary method, the descriptive method, the method of repetition. To give a better follow-up and control of the different techniques and instruments, the tests and the functional assessment sheets of the instrumental and basic activities of daily life (Barthel and Lawtopn - Broddy) and the physical pre and post test. In the research we worked with a group of 17 older adults who attended the club of grandparents in the movement of the Obrapia neighborhood, which came to obtain and the result as: The lack of scheduled physical activity does not allow the development of independently compliance with the instrumental and basic activities of daily life In the elderly of the grandparents club in motion. Once the results are reached: all older adults should participate in clubs, where planned physical activities are developed, to improve compliance with the instrumental and basic activities of daily life and have a better quality of life in the aging stage.